TANTANGAN INDUSTRI COLD SUPPLY CHAIN PRODUK MAKANAN BEKU - Yuli Evitha (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
The purpose of this paper is to analyze the challenges faced by the cold supply chain industry in Indonesia, especially for frozen food products. The challenges faced are temperature control in storage and distribution and the food distribution speed. This is due to inadequate infrastructure conditions in Indonesia. It is suggested that the government should build and improve infrastructure and provide incentives such as tax incentives, given that the cold supply chain industry is very expensive.